Pembuatan Robot Pengikut Garis Dengan Perintah Suara - Sofyan Lukmanfiandy; Suharyanto Suharyanto (Informasi Interaktif, 2016)
Line follower robot with a standing order is a robot that uses protodioda and condensor as a sensor. Protodioda can work with the help of LED that serves as the light source. LDR is placed at the bottom of the robot and arranged so that the LED light is directed to the floor in a position right under the fall of LDR (Light Dependent Resistor). Surface of a line have different light reflectivity, white surface has a reflectivity greater than the black surface. This line follower robot can walk on the path are black with a white floor surface. LDR will have a large resistance value if it is a dark place and will decrease the value of resistance, if it is a bright place, with different reflectivity that is the concept of censorship in this line follower robot. Functioned as a sound sensor switch On / Off of the current source driver circuit to the robot, so the robot can walk and stop with voice commands. Keyword: robot pengikut garis, sensor suara